2014
DOI: 10.5424/sjar/2014121-4926
|View full text |Cite
|
Sign up to set email alerts
|

Mixed model with spatial variance–covariance structure for accommodating of local stationary trend and its influence on multi-environmental crop variety trial assessment

Abstract: The most common procedure for analyzing multi-environmental trials is based on the assumption that the residual error variance is homogenous across all locations considered. However, this may often be unrealistic, and therefore limit the accuracy of variety evaluation or the reliability of variety recommendations. The objectives of this study were to show the advantages of mixed models with spatial variance-covariance structures, and direct implications of model choice on the inference of varietal performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Costa et al (2005) found no significant differences between the spherical, exponential and Gaussian models for the estimates of variance components. However, Duarte & Vencovsky (2005), evaluating the efficiency of spatial statistical analysis in the selection of soybean genotypes, found similar results to those of experiment 7, significant spatial autocorrelation by the DW test, and best fit for the exponential model with a range of 20.4 m. In the study of Negash et al (2014), the exponential model also showed the best quality fit for most of the evaluated trials.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Costa et al (2005) found no significant differences between the spherical, exponential and Gaussian models for the estimates of variance components. However, Duarte & Vencovsky (2005), evaluating the efficiency of spatial statistical analysis in the selection of soybean genotypes, found similar results to those of experiment 7, significant spatial autocorrelation by the DW test, and best fit for the exponential model with a range of 20.4 m. In the study of Negash et al (2014), the exponential model also showed the best quality fit for most of the evaluated trials.…”
Section: Resultssupporting
confidence: 53%
“…Thus, the randomized blocks design may not be effective to control the spatial variability present in trials of genetic evaluation. Negash et al (2014) pointed out that several factors contribute to the spatial variability in experimental areas used for genetic evaluation of plants, including fertility changes, pH, soil structure and incidence of diseases and pests. The authors carried out a very detailed study addressing the advantages of using mixed models, considering the data's spatial structure, in trials of plant genetic evaluation in different environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The R ij matrix was modeled by a spatial covariance structure based on the decompositions of error effects ε ij separately for the j th location in the i th year into a spatially dependent residual ξ ij and a spatially independent residual η ij (noise effects). For ξ ij , we assumed a separable autoregressive covariance structure (AR1 × AR1) in rows and columns (Cullis et al, 1998; Negash et al, 2014; Stefanova et al, 2009): boldnormalR ij = normalσ normalξ ij 2 [ AR1( normalΦ col )AR1( normalΦ row ) ]+ normalσ n ij 2 I where normalσ normalξ ij 2 is the variance of spatially correlated residuals ξ ij for the j th location in the i th year, is the variance of independent residuals η ij for the j th location in the i th year, I is the identity matrix, and AR1 (Φ col ) and AR1 (Φ row ) are the first‐order autoregressive correlation matrices with autocorrelation parameters Φ col and Φ row , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The R ij matrix was modeled by a spatial covariance structure based on the decompositions of error effects e ij separately for the jth location in the ith year into a spatially dependent residual x ij and a spatially independent residual h ij (noise effects). For x ij , we assumed a separable autoregressive covariance structure (AR1 ´ AR1) in rows and columns (Cullis et al, 1998;Negash et al, 2014;Stefanova et al, 2009):…”
Section: Linear Mixed Modelsmentioning
confidence: 99%